Study of issues of attitude to the place and role of women of Uzbekistan in society in the XX century - Nilufar Dalibayevna Djuraeva (Universitas Muhammadiyah Sidoarjo, 2019)
The article analyzes the place and role of women in society in the twentieth century and their social status. At the beginning of the twentieth century, the views of Turkestan jadids on this issue, the study of women's problems in the Soviet period and the importance of state policy towards women in the years of independence were covered from a scientific point of view.